Cellulase Production from Trichoderma harzianum: a Framework Modeling for Evaluating Different Operating Mode Strategies (2021)
The cellulase enzyme has been used in essential applications in the textile industry and the formulation of some medicines. Therefore, a mathematical model based on previous reports is proposed for cellulase enzyme enhancement. First, the kinetic constants were taken from the literature. Then, two operating strategies were carried out to maximize cellulase production using 10g/L of cellulose and 0.4g/L of cells as a first strategy using a batch mode. Alternatively, a second operating mode is simulated using continuous cellulose feeding. Finally, a comparative analysis was made for determining the best operating mode related to maximal cellulase production. Interestingly, the continuous mode shows a high cellulase concentration lasting a shorter time than the batch mode to avoid inhibiting enzyme production. One of the most important findings of this work focuses on increasing cellulase production with values of 1800 FPT/L simulating the continuous mode. The latter suggests that cellulase production could be double the concentration obtained with the traditional batch mode (800FPU/L). Results obtained in this research may be promising for the enzyme production industry. Using simulation techniques, it is possible to determine an enhancement without requiring excessive experimentation and resources.